The Activities of Cross - Functional Teams of Central Officials, Community Development Department - Poonsawat, Chaiyapleuk; Lumpungjit, Kunprapat; Jaipheng, Phatharaporn; Tosamphan, Puncharat; Sutes, Somchay (Journal of Graduate MCU KhonKaen Campus, 2023)
The objectives of this research were to study (1) the factor of cross-functional teams on working of central officials, Community Development Department; (2) the efficiency on working of central officials, Community Development Department; and (3) the approach for developing efficient cross-functional team on working of central officials, Community Development Department. The researcher collected data by using the mixed-methods research. The quantitative sample were community development officials in central office, totals of 190 people, which collected data by questionnaires, and the qualitative informants, totals of 30 people, consisting of 15 people of workgroup directors and 15 people of operational officials, which collected data by in-depth interviews. The results of study revealed that the overall of factor of the cross-functional team performance was at high level (4.10), with the issue of Work Skills of Team Members (4.15) had the highest average, the follow issues ordered by average were, Interaction within the Team (4.12), Role in the Team (4.10), and the Management System of the Team (4.01). As for the overall of efficiency on working was at a high level (4.24), with the Workload (4.34) had the highest average, the follow issues ordered by average were, Quality of Work (4.23), Cost (4.21), and Timing (4.19). As for the approach for improving the efficiency of cross-functional team, there must be continuous communication within the cross-functional team for participating on planning to achieve the goals, including the team should develop more techniques for working conveniently and quickly.